Selection of alpha/beta interferon- and gamma interferon-resistant rickettsiae by passage of Rickettsia prowazekii in L929 cells. - Turco, J (1990)
The ability of endogenously produced alpha/beta interferon (IFN-alpha/beta) to inhibit rickettsial growth in infected L929 cell cultures was evaluated by comparing the growth of Rickettsia prowazekii Madrid E in untreated cultures and cultures treated with anti-mouse IFN (alpha + beta) serum. The endogenously produced IFN was neutralized, and rickettsial growth was enhanced in the antiserum-treated cultures. This inhibitory effect of endogenously produced IFN-alpha/beta was used to select rickettsiae resistant to IFN-alpha/beta. Rickettsiae were screened for resistance to IFN-alpha/beta after being cultured in untreated L929 cells for several weeks to several months. Two isolates derived from R. prowazekii Madrid E and two isolates derived from plaque-purified R. prowazekii Madrid E were plaque-purified twice, grown in embryonated hen eggs, and evaluated for resistance to IFN-alpha/beta and IFN-gamma. Compared with the parental rickettsial strain, all four isolates were significantly resistant to IFN-alpha/beta and IFN-gamma. In addition, they were as resistant or more resistant to IFN-gamma when compared with two previously described IFN-gamma resistant isolates that were selected in IFN-gamma-treated L929 cells. One of the two isolates from IFN-gamma-treated L929 cells was also resistant to IFN-alpha/beta; the other isolate was similar to the parental Madrid E strain in sensitivity to IFN-alpha/beta.